(untitled) (British Journal of Global Ecology and Sustainable Development, 2024)
This article examines one of the main works of Shihabiddin Abuhafs Umar Suhrawardi, “Aworif-ul-maorif”, containing moral and educational ideas. The Sufis’ views on the moral norms underlying their behavior and on the etiquette of the teacher-student also fall under the analysis.